The Infusion of Science into Sustainable Lifestyles Project: A Case Study of Implementing a Merdeka Curriculum at Six Sekolah Penggerak in West Java - Nurhayati, Pipih; Rochintaniawati, Diana; Yustiana, Yusi Riksa (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The Infusion of Science into Sustainable Lifestyles Project was a case study conducted in six elementary schools in West Java, Indonesia to examine the implementation of a Merdeka Curriculum. A project aimed at increasing students' awareness of the principles of Pancasila, a set of national values, and promoting sustainable lifestyles. The study used a case study research method, including observations, interviews, and document analysis, to understand the development and implementation of the project. The results showed that the project included a variety of activities, such as games, simulations, and discussions, to engage students and help them understand the principles of sustainable living. The study also found that integrating science content, such as information about ecosystems and the environment, was an effective way to enhance the sustainability theme of the project. The researchers concluded that the Infusion of Science into Sustainable Lifestyles Project was successful in promoting sustainable lifestyles among students and recommended continued implementation and evaluation of the project in the future.